Efektivitas Rekam Medis Elektronik dalam Menunjang Kinerja di Instalasi Rekam Medis RSUD Provinsi NTB - Sukriani Sukriani; Menap Menap (Universitas Malahayati, 2026)
ABSTRACT Digital transformation in the healthcare sector is one of the government's steps to improve service quality, one of which is through the implementation of Electronic Medical Records (EMR) in various healthcare facilities. EMR is an innovative solution to support work efficiency, speed of information access, and accuracy of medical data recording. The NTB Provincial Hospital, as a provincial referral hospital, has implemented the EMR system since December 2023. However, the effectiveness of its implementation still needs to be assessed determine its actual impact in improving the performance of the Medical Records Installation. This study aims to evaluate the extent to which the EMR system supports the effectiveness of medical records installations in terms of accelerating administrative services, accurately recording patient information, facilitating data access between service units, and saving time and money. Furthermore, this study also aims to identify various obstacles encountered during the implementation process. This research used a descriptive qualitative method with a case study approach, conducted at the Medical Records Installation of the NTB Provincial Hospital in June 2025. The research informants consisted of 10 people consisting of medical records officers, installation heads and RME system technicians selected through purposive sampling techniques. Data collection techniques were carried out through semi-structured interviews and analyzed using thematic analysis techniques. The use of EMR was deemed quite effective in accelerating patient data recording and retrieval, improving the accuracy of medical information, and streamlining coordination between units. However, the implementation of the EMR system still faces several challenges, such as limited technological infrastructure, suboptimal integration of the EMR system with other platforms, and minimal training provided to staff. Improving managerial support, strengthening human resource training, and developing a more integrated system are factors worthy of attention to ensure the sustainability of EMR implementation as expected. Keywords: Medical Records Installation, Performance, Electronic Medical Records (EMR). ABSTRAK Transformasi digital dalam sektor kesehatan menjadi salah satu langkah pemerintah untuk meningkatkan kualitas pelayanan, salah satunya melalui implementasi Rekam Medis Elektronik (RME) di berbagai fasilitas layanan kesehatan. RME sebagai solusi inovatif dalam mendukung efisiensi kerja, kecepatan akses informasi, serta akurasi pencatatan data medis. RSUD Provinsi NTB, sebagai rumah sakit rujukan tingkat provinsi, telah mengimplementasikan sistem RME sejak Desember 2023. Namun, pelaksanaannya masih perlu dikaji untuk memastikan bagaimana dampaknya secara menyeluruh terhadap peningkatan kinerja di Instalasi Rekam Medis. Penelitian ini bertujuan untuk mengevaluasi sejauh mana sistem RME menunjang efektivitas kerja instalasi rekam medis dalam hal percepatan layanan administrasi, ketepatan pencatatan informasi pasien, kemudahan akses data antarunit pelayanan, serta efisiensi waktu dan biaya. Selain itu, penelitian ini juga bertujuan mengidentifikasi berbagai faktor kendala yang dihadapi selama proses implementasi. Penelitian ini menggunakan metode kualitatif deskriptif dengan pendekatan studi kasus, dilaksanakan di Instalasi Rekam Medis RSUD Provinsi NTB pada Juni 2025. Informan penelitian berjumlah 10 orang yang terdiri dari petugas rekam medis, kepala instalasi dan teknisi sistem RME yang dipilih melalui teknik purposive sampling. Teknik pengumpulan data dilakukan melalui wawancara semi terstruktur dan dianalisis menggunakan teknik thematic analysis.Penggunaan RME dinilai cukup efektif dalam mempercepat pencatatan dan pencarian data pasien, meningkatkan akurasi informasi medis, serta memperlancar koordinasi antarunit. Namun demikian, penerapan sistem RME masih menghadapi berbagai kendala, seperti keterbatasan infrastruktur teknologi, belum optimalnya integrasi sistem RME dengan platform lain, serta minimnya pelatihan yang diberikan kepada petugas. Peningkatan dukungan manajerial, peningkatan pelatihan sumber daya manusia dan pengembangan sistem yang lebih terintegrasi menjadi faktor yang patut diperhatikan guna menjamin keberlanjutan implementasi RME sesuai yang diharapkan. Kata Kunci: Instalasi Rekam Medis, Kinerja, Rekam Medis Elektronik (RME).